Tantangan Cyberbullying di Kalangan Remaja Analisis di Era Teknologi 21 - Muhammad Ikhsan (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Cyberbullying has become a significant problem among teenagers along with the rapid development of information and communication technology in the 21st century. This research aims to analyze the challenges faced by teenagers due to the cyberbullying phenomenon, including its impact on mental health, social relationships and daily behavior. Through qualitative and quantitative methods, data was collected from surveys and interviews with teenagers in various secondary schools. The research results showed that almost 40% of respondents had experienced or witnessed cyberbullying, with varying impacts, ranging from anxiety to depression. In addition, factors such as anonymity in cyberspace, low awareness of negative impacts, and the influence of social media contribute to increasing cases of cyberbullying. This research recommends educational approaches and community interventions to increase awareness and understanding of cyberbullying among adolescents, as well as the importance of support from parents and teachers in creating a safe and positive environment in the digital world.